2015
DOI: 10.1136/neurintsurg-2015-011788
|View full text |Cite
|
Sign up to set email alerts
|

Distal access using hyperflexible atraumatic distal tip with optimized proximal stability of the Benchmark intracranial guide catheter for the treatment of cerebral vascular diseases: a technical note

Abstract: Background A stable guide catheter position within the intracranial vasculature is critical for safe, successful endovascular treatment. Objective To present ourinitial experience with the 0.071 inch inner diameter Benchmark guide catheter used in the treatment of intracranial cerebrovascular pathologies, demonstrating its safety and efficacy. Methods We retrospectively reviewed use of the Benchmark guide catheter from September through December 2014 in the management of various neuroendovascular intracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 10 publications
0
22
1
Order By: Relevance
“…Chandran et al reported that kickback of DAC occurred after the procedure, 2) but no kickback was clearly noted in our study, clarifying superior supportability of DD6. DD6 itself acquired a 3D shape due to the shaping and had a fulcrum, being stable, when it was placed in the distal blood vessel, which may also have contributed to the supportability.…”
Section: Disclosure Of Statementcontrasting
confidence: 40%
See 2 more Smart Citations
“…Chandran et al reported that kickback of DAC occurred after the procedure, 2) but no kickback was clearly noted in our study, clarifying superior supportability of DD6. DD6 itself acquired a 3D shape due to the shaping and had a fulcrum, being stable, when it was placed in the distal blood vessel, which may also have contributed to the supportability.…”
Section: Disclosure Of Statementcontrasting
confidence: 40%
“…Improvement of the stability and safety of intracranial device operation by the use of DAC as a coaxial system has been reported, [4][5][6] but to apply the adjunctive techniques described above, a 6Fr or larger catheter is necessary. In western countries, several types of 6Fr or larger DAC are now used, 2,3) but in Japan, at present, only DD6 is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the Cat5 catheter is intended to be used as part of a tri-axial system, and it would not be sufficient as the primary guide catheter in a bi-axial system for a transfemoral approach to the cerebral circulation. Other centers have published use of the Benchmark catheter (Penumbra) as part of a bi-axial system for PED cases and other aneurysm treatments [14,15]. Our group prefers tri-axial systems for their greater flexibility (more possible catheter combinations for various anatomy) and improved distal access.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported the usefulness of a method to use an intermediate support catheter as a co-axial system in patients with a specific distance to the lesion site, [11][12][13] as demonstrated in the present case. As its merits, the operability of a microcatheter may be improved by reducing microcatheter friction/resistance at the flexed area of an access blood vessel, and an improvement in the supporting performance of a guiding system may facilitate an access to the lesion site.…”
Section: Discussionmentioning
confidence: 82%